PERANCANGAN APLIKASI PENGELOLAAN CETIYA RUMAH DHAMMA CIBUBUR BERBASIS WEBSITE - Vikaliendry Nathayana; Tony (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
The advancement of information technology (IT) has transformed how information is disseminated, including within the religious sector. Cetiya Rumah Dhamma Cibubur, a Buddhist place of worship, faces challenges in managing its activities and information effectively. Currently, information is shared through WhatsApp groups and social media, which is inefficient and limits congregational engagement. This research aims to develop a website-based information system to improve activity management, congregation data, attendance, and donations at Cetiya Rumah Dhamma Cibubur. The Agile model within the Software Development Life Cycle (SDLC) was used for flexible, iterative development. The website was built with NextJS for the front-end, Golang for the back-end, and MySQL for database management. The results show that the website resolves communication and information management issues, offering features like event management, data handling, attendance tracking, and donations. The website is responsive, accessible across devices, and enhances operational efficiency, access to information, and participation in religious activities.